Acute Leukemias IX: Basic Research, Experimental Approaches and Novel Therapies - Hiddemann, Wolfgang (Haematology and Blood Transfusion Hämatologie und Bluttransfusion, 2003)
Acute Leukemias IX provides an extended and thorough overview of recent developments in cell biology and experimental therapy for acute leukemias. Following the tradition of the Acute Leukemias series since 1987, this book bridges the gap between basic research and clinical studies and emphasizes that both aspects are equally necessary to achieve improvements, not only in understanding the disease but also in providing better therapy. As a forum for world-wide activities in the field of acute leukemias the volume contains invaluable contributions that provide the reader with new, previously unpublished information